2005
DOI: 10.1111/j.1399-0004.2006.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Germline MSH2 and MLH1 mutational spectrum including large rearrangements in HNPCC families from Poland (update study)

Abstract: Germline mutations in the DNA mismatch repair genes MSH2 and MLH1 account for a significant proportion of hereditary non-polyposis colorectal cancer (HNPCC) families. One approach by which development of an efficient DNA-testing procedure can be implemented is to describe the nature and frequency of common mutations in particular ethnic groups. Two hundred and twenty-six patients from families matching the Amsterdam II diagnostic criteria or suspected HNPCC criteria were screened for MSH2 and MLH1 germline mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…In these genes (MSH2, MLH1, PMS2, and MSH6), the majority of causative mutations (90%) have been found in MSH2 (MIM] 120435; GenBank: NM_000251.1) and MLH1 (MIM] 120436; GenBank: NM_000249.2) [Kurzawski et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…In these genes (MSH2, MLH1, PMS2, and MSH6), the majority of causative mutations (90%) have been found in MSH2 (MIM] 120435; GenBank: NM_000251.1) and MLH1 (MIM] 120436; GenBank: NM_000249.2) [Kurzawski et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Q402X is a stop mutation that was previously identified in an LS kindred from Poland [18] and we have identified it here for the first time here in association with PC. Whether K618A is pathogenic remains a debated question.…”
Section: Discussionmentioning
confidence: 74%
“…Consequently, genetic testing for abnormalities in susceptible genes and the organization of the registries of CRC families are gaining increased popularity worldwide. Large genetic studies performed in Poland have revealed that fifty MSH2 and MLH1 mutations were characteristic for the local population [13]. Our previous study had demonstrated that these abnormalities were also present in the Lower Silesian population [14].…”
Section: Discussionmentioning
confidence: 99%